New applicator saves fertilizer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A hand-operated machine that buries fertilizer some 5 cm below the surface of rice paddies should enable a farmer to halve his fertilizer costs yet still maintain his yield levels. Spreading fertilizer in the conventional way on paddies is very...